KARAKTERISTIK DAN JENIS KENDARAAN LOGISTIK DI INDONESIA - Ni Putu Decy Arwini; I Putu Kresna Suputra (WidyaTeknik, 2026)
Industrial activities, starting from the initial activity, namely the process of procuring raw materials, to the distribution of finished goods (fine goods), require transportation to move products from their place of origin to their destination. Not only for the products to be produced but also transportation activities support worker mobility which is the main factor in industrial activities. Therefore, it can be said that transportation itself is an integral part of the industrial world. In the industrial world, the term logistics is known. Logistics is an integrated system that coordinates all processes within an organization or company in preparing and delivering products or goods to consumers. In other words, all processes in an industry are logistics activities. According to the World Bank's 2023 Logistics Performance Index (LPI), Indonesia ranked 59th out of 140 countries, with a Logistics Performance Index (LPI) score of 3.0. This is far below Singapore, which holds the top spot with an LPI score of 4.3. Logistics transportation permitted to operate in Indonesia, especially land transportation modes, range from small vehicles such as pick-ups, single axle trucks, CDC trucks, tronton trucks, trintin trucks, trinton trucks to container trucks that can be adjusted to the needs of the industrial products to be transported or the distance to be traveled. There are separate rules that must be followed by logistics transportation vehicles in Indonesia, for example, rules regarding permitted vehicle traffic hours, the number and weight of permitted loads, the types of vehicles allowed to pass through a road section and so on.